PERSEPSI IBU TERKAIT PEMANFAATAN PELAYANAN ANTENATAL CARE DI KOTA KUPANG - Maria Lupita Nena Meo (Jurnal Kesehatan Reproduksi, 2018)
Background: A minimum standard of antenatal care visit is four times with the first visit (K1) as early as possible since the delayed menstrual period. Delayed access to antenatal care could influence the outcome of childbirth. Objective: This study was aimed to explore mothers’ perceptions regarding utilization of Antenatal care services in order to identify the reasons why mothers are late to access antenatal care and what are the barriers in accessing antenatal care. Method: A qualitative study with a phenomenological approach was conducted in this research. Data were collected using an in-depth interview in Oepoi primary health care center which had the lowest K1 and K4 coverage. Six main informants and two supporting informants were obtained using a purposive sampling technique and we also handle triangulation of source. Results: The cause of delay in accessing ANC services begins with the mothers' lack of understanding regarding the pregnancy which leads to the failure to recognize, plan, and accept the pregnancy. Another cause is socio-cultural factor related to the status of women in family and society. The family's economic status and inadequate ANC services experience are also considered to influence accessibility to ANC services. Conclusion: The three main problems that caused the delay in accessing antenatal care services are mothers' perception of pregnancy, mothers' perception of ANC services, and mothers' perception of accessibility to ANC services. Therefore, this study suggests health care providers to continuously provide information regarding the benefits and standards of ANC services in order to change the perception of the mother, family and society.